A comparison of the effects of two different grazing systems on community attributes of eastern Karoo vegetation - Hallward, Jennifer R (Not Specified, 2023)
Soil erosion is regarded as a serious problem throughout the world. Erosion is. caused by both water and wind. Al though the two usually occur ·together, wind erosion has received little attention with the exception of the problems associated with croplands. Wind erosion can, however, also be a serious problem in natural grazing lands. In this research project an attempt is made to . determine the areas of potential wind erosion in the Cape Province through the use of two different models. The models used were developed and applied in semi-arid areas and thus were considered to be applicable in South Africa. The models used are: The Wind Erosion Equation developed by Chepil, ·woodruff and Sideway in the United States; and Lynch and Edward's Model for the Analysis of Limited Climatic Data, developed in Australia. There are two aspects to soi 1 erosion by wind - the erodibility of the soil as determined by moisture, grains size, aggregates, plant cover and surface topography; and soil erosive ty as determined by wind strength and duration. Methods to control wind erosion are based on decreasing erosivity through the establishment of shelterbelts and by decreasing erodibility ty through improving plant cover, aggregate stability and moisture retention properties. Efforts at wind erosion measurement are generally ineffective. A number of models have been developed to overcome these difficulties and to allow for prediction of soil loss. Two of these models are applied to conditions in the Cape Province. This area covers a wind range of climatic, soil and agricultural conditions and as such provides an appropriate area for their application. It is, however, concluded that neither of these models can be directly applied to conditions in the Cape Province. The seasonal rainfall distribution and the uneven distribution of the data points contribute to the ineffectiveness of the models. The greatest problem, however, is the importance of management in determining whether or not wind erosion occurs. As a result, although the models illustrate the general climatic trends affecting the susceptibility of an area to wind erosion, the lack of a management factor accounts for the lack of detail.